Pencarian Klasifier Terbaik sebagai Solusi Rekrutmen Karyawan Menggunakan Algoritma Iterative Dichotomiser 3 (ID3) - Ramadhani, Nilam; Syahroni, Abd. Wahab; Darmawan, Irwan (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2022)
CV Aliyah Mandiri Pamekasan is a growing distribution fabric and apparel company. The worker is drawn through the employee recruitment process by passing a series of tests.But sometimes there is a subjectivity factor that becomes problem in recruitment process even criterias have been established. To avoid that,needed a system tahat can help HRD manager to decide which applicants are eligible for admission.One of them is Decision Tree. This method can find discrete  approximation function and resistant to noise data. Also able to study disjunctive expressions. The Iterative Dychotomizer 3 (ID3) algorithm can build a top-down decision tree using information gain as a measure of the effectiveness of an attribute in classifying incomplete data sample sets. The results of the algorithm implementation can provide the best classifier knowledge on employee recruitment, so that it provides decision support considerations.